Looking Both Ways - Holtzen, Wm. Curtis; Wilgus, J. Blair; Yuile, James; Carman, Jon; Toney, Carl N. (Claremont Press, 2023)
This volume explores a variety of topics in biblical studies, ministry, and pedagogy from perspectives inspired by Joseph Grana II.